Reciprocal effects of motivation in physical education and self-reported physical activity. (July 2017) - Taylor, Ian M.
Abstract: Objectives: The present study tested whether self-reported school and leisure-time physical activity have a reciprocal relationship with Physical Education (PE)-based motivational regulations described by self-determination theory. Participants were 635 11- and 12-year-old school children from the United Kingdom. Design & Method: A cross-lagged longitudinal design over two time points was employed. Study hypotheses were analyzed using latent factor reciprocal effects models. Results: Following temporal invariance tests, data revealed positive relationships between both types of physical activity and subsequent changes in autonomous motivation, but not the oft-stated reverse relationship. No relationships were observed involving introjected regulation. Theoretically aligned relationships between external regulation and changes in physical activity were observed, but no reverse relationships. Both types of physical activity behavior were negatively associated with changes in amotivation in PE, but surprisingly, amotivation in PE positively predicted changes in leisure-time physical activity. Conclusions: In general, physical activity participation may help children internalize reasons for partaking in PE and foster self-determination. However, the widespread theory that self-determined PE motives can develop school and leisure-time physical activity participation was not compellingly demonstrated. Highlights: Amotivation in PE unexpectedly predicted increases in leisure-time physical activity. Physical activity participation may help foster self-determination towards PE. The proposal that autonomous PE motivation can help facilitate increases in physical activity was not supported.